Místo osobností z protestantského prostředí v české kultuře po roce 1918 - Putna, Martin C. (Lidé města, 2008)
The Czech National Revival heavily exploited the rhetoric of the Czech Reformation, yet the real Protestant Churches remained in the position of a small isolated „milieu“, in numbers as well in intellectual creativity. Since 1918, the independent Czechoslovak Republic created a more supportive background for the growth of Czech Protestantism. The article presents the three main areas of its intellectual and cultural creativity. First, the development of Czech Protestant theology. The liberal theology represented is the major theological stream. The liberal theologians (J. B. Kozák, F. Linhart and others) considered T. G. Masaryk to be the central religious thinker of the time. To them, following Masaryk meant the reinterpreting of Christianity according to modern science (Jesus as a mere teacher of ethics et cetera). Against this tendency, the young theologian J. L. Hromádka introduced a renewed Protestant Orthodoxy in the steps of Swiss theologian Karl Barth. For this purpose, Hromádka used his journal Křesťanská revue (Christian revue). The younger generation of Czech Protestants mostly followed Hromádka, and not the liberals. Secondly, the development of Czech Protestant historiography. The most vociferous representative of Protestant historical studies, F. M. Bartoš, presented the history of Czech reformation in a highly polemical way, mixing historical science with a journalistic anti-Catholic agitation. Other historians of Protestant background (K. Krofta, O. Odložilík) were capable to put together their engagement in the Protestant Church with scientific objectivity, and thus to present their subjects, taken from the history of Czech Reformation, in a non-polemical and non-anti-Catholic way. Thirdly, the relation of the Protestant milieu to the literary criticism and to the literary creativity. Literary historian J. B. Čapek was the only member of Protestant circles with a lasting interest for the Protestant tradition in Czech literature. His main work, Československá literatura toleranční 1781-1861, offered a new approach to the history of Czech literature, based on the continuity of writing in Czech language both in the Czech lands and in Slovakia. However, his effort to initiate a new artistic creativity in Czech Protestant circles was not successful. Instead, the debate in the journal Křesťanská revue (between Čapek himself, Hromádka, E. Rádl and others as participants) demonstrated that only few representatives of the Protestant milieu were ready to concede the autonomy of modern literature and arts. The article concludes that the Protestant milieu was in all discussed areas deeply divided in its relation to the modern world, always wavering between „internal“ and „external“ values.